CONTENTS OF SERUM MYELIN BASIC PROTEIN-IGG ANTIBODIES COMPLEXES IN NORMAL PREGNANCY AND GESTOSIS - V. G. Levchenko (SPb RAACI, 2014)
Serum levels of myelin basic protein (MBP)-bound immune complexes were studied in blood sera from women with gestosis, as compared with those in normal pregnancy and non-pregnant woman. The amounts of IgG-MBP complex in blood serum were determined by enzyme immunoassay using isolated anti-МBP-antibodies. The study has shown that about 0.05 mcg of IgG ml of blood serum are associated with myelin basic protein in unpregnant women or in normal pregnancy. Mild gestosis is accompanied by a 2-3-fold increase in MBP immunocomplex concentrations in blood serum. More severe stages of gestosis are characterized by its further rise, thus achieving maximal values of such MBP immune complexes (0.8 mcg/ml) in patients with pre-eclampsia and eclampsia. Their amounts were reduced twice after the periods of eclampsia. Serum levels of MBP-bound IgGs may be used to determine severity of gestosis and to predict a risk of eclampsia in pregnant women.